PENGARUH KUALITAS PELAYANAN DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP KEPUASAN PELANGGAN DI PT. PINDO DELI PAPER PRODUCT - Dhea Fitria; Gemilang Fhajri Arye; Muhammad Nazif (BTJ : Business and Technology Journal, 2024)
This report aims to analyze the influence of service quality and timeliness of delivery on customer satisfaction at PT. Pindo Deli Paper Products. The research sample is all customers of PT. Pindo Deli Paper Products. This research is a descriptive research method with a qualitative approach, the results obtained from the research are that service quality has a significant effect on customer satisfaction, timeliness of delivery has a significant effect on customer satisfaction, service quality and timeliness of delivery have a simultaneous effect on customer satisfaction. The resulting implications can help companies to better understand customer needs and expectations, so they can optimize customer needs and strengthen the company's market.Keywords: service quality, on time delivery, customer satisfaction